Circumstances of Internet Addiction and Its Influencing Factors among Adolescents in the Second Years of the Covid-19 Pandemic - Tanjung, Ika Citra Dewi; Lili Rohmawati (Universitas Airlangga, 2023)
Background: Internet use by adolescents has increased rapidly in recent decades. This has been particularly evident during the Covid-19 pandemic due to the shift from face-to-face to online learning. Internet use has become convenient and commonplace. However, negative use can cause internet addiction, which interferes with brain or mental function in everyday life. Purpose: The aim of this survey is to analyze the prevalence of internet addiction and the factors that affect it. Methods: This cross-sectional analytical survey was conducted online with adolescents living in the city of Medan, North Sumatra, from August to November 2021. The demographic data came from a self-reported structured questionnaire, and internet addiction was assessed using the Internet Addiction Diagnostic Questionnaire (KDAI) in Indonesian. The data were processed with descriptive statistics and presented in the form of frequency distribution. Factors affecting the occurrence of internet addiction were analyzed using nonparametric tests. Results: Among the 110 adolescent respondents, the prevalence of internet addiction was 40.0%. The majority of those experiencing internet addiction had a high-school education (56.8%) and were girls (52.3%), firstborn (41.0%), and aged 17–19 (40.9%). The total daily and weekend internet use levels were medium (81.8% and 61.4%, respectively). Total daily internet use time was a statistically meaningful factor affecting the occurrence of internet addiction in adolescents (p = 0.014). Conclusion: The prevalence of internet addiction in adolescents is quite high, and total daily internet use was a factor affecting it.